Neuronal ApoE4 in Alzheimer’s disease and potential therapeutic targets - Zhang, Lan; Xia, Yiyuan; Gui, Yuran (Frontiers in Aging Neuroscience, 2023)
The most prevalent genetic risk factor for Alzheimer’s disease (AD) is Apolipoprotein E (ApoE), a gene located on chromosome 19 that encodes three alleles (e2, e3, and e4) that give rise to the ApoE subtypes E2, E3, and E4, respectively. E2 and E4 have been linked to increased plasma triglyceride concentrations and are known to play a critical role in lipoprotein metabolism. The prominent pathological features of AD mainly include senile plaques formed by amyloid β (Aβ42) aggregation and neuronal fibrous tangles (NFTs), and the deposited plaques are mainly composed of Aβ hyperphosphorylation and truncated head. In the central nervous system, the ApoE protein is primarily derived from astrocytes, but ApoE is also produced when neurons are stressed or affected by certain stress, injury, and aging conditions. ApoE4 in neurons induces Aβ and tau protein pathologies, leading to neuroinflammation and neuronal damage, impairing learning and memory functions. However, how neuronal ApoE4 mediates AD pathology remains unclear. Recent studies have shown that neuronal ApoE4 may lead to greater neurotoxicity, which increases the risk of AD development. This review focuses on the pathophysiology of neuronal ApoE4 and explains how neuronal ApoE4 mediates Aβ deposition, pathological mechanisms of tau protein hyperphosphorylation, and potential therapeutic targets.